PENGARUH DANA PIHAK KETIGA, KECUKUPAN MODAL, RISIKO KREDIT DAN SUKU BUNGA KREDIT TERHADAP PROFITABILITAS BANK BUMN TAHUN 2010-2012 - Anggreni, Made Ria; Suardhika, Made Sadha (E-Jurnal Akuntansi, 2014)
Bank to conduct operations has the main objective, namely to achieve a maximum level of profitability. Profitability is the ability of banks to generate profit with effectively and efficiently. The purpose of this study was to determine the effect of third -party funds, capital adequacy is measured by Capital Adequacy Ratio (CAR), credit risk is measured by non-performing loans (NPL), loan interest rates to the profitability of the state-owned banks in Indonesia . This study used a sample that is saturated with all members of the population sabagai taking samples. The data is monthly data obtained from published financial statements of state banks in accordance for three years ie 2010-2012. The data analysis technique used is multiple linear regression analysis techniques. The results showed variable CAR deposits and a positive influence, while the NPL and Interest Rates negative effect on profitability (ROA).
Keywords: third -party funds, CAR, NPL, lending rates, ROA